Self-incompatibility in Papaver: identification of the pollen S-determinant PrpS. (22nd March 2010) - Poulter, Natalie S.; Wheeler, Michael J.; Bosch, Maurice; Franklin-Tong, Vernonica E.
Abstract : Many flowering plants are hermaphrodite, posing the problem of self-fertilization and the subsequent loss of the genetic fitness of the offspring. To prevent this, many plants have developed a genetically controlled mechanism called self-incompatibility (SI). When the male and female S -determinants match, self (incompatible) pollen is recognized and rejected before fertilization can occur. In poppy ( Papaver rhoeas ), the pistil S- determinant (PrsS) is a small secreted protein that interacts with incompatible pollen, initiating a Ca 2+ -dependent signalling network. SI triggers several downstream events, including depolymerization of the cytoskeleton, phosphorylation of two soluble inorganic pyrophosphatases and an MAPK (mitogen-activated protein kinase). This culminates in PCD (programmed cell death) involving several caspase-like activities. The recent discovery of the Papaver pollen S -determinant PrpS marks a significant step forward in the understanding of the Papaver SI system. PrpS encodes a 20 kDa predicted transmembrane protein which has no homology with known proteins. It is specifically expressed in pollen, linked to the pistil S- determinant, and displays the high polymorphism expected of an S- locus determinant. The present review focuses on the discovery and characterization of PrpS which strongly support the hypothesis that Papaver SI is triggered by the interaction of PrsS and PrpS.